Implementasi Metode MAUT pada Sistem Penunjang Keputusan dalam Perancangan Sistem E-Voting Pemilihan Calon Ketua OSIS - Trisudarmo, Ragel; Nursyamsu, Roni; Wati, Dyah Puteria (Jurnal Sistem Informasi Bisnis, 2024)
The process of selecting a chairman in an organization within the school environment is an important moment for students in training and developing leadership skills and understanding of a democratic system where every student has equal voting rights to elect a candidate for OSIS chairman who is considered good and capable. In order to get competent and qualified candidates for chairman or prospective chairman, system implementation is required. So far, the process of selecting prospective chairman is considered not serious and does not pay attention to the requirements or supporting aspects possessed by all prospective candidates. So far, it is still carried out subjectively. Therefore, it is necessary to implement a decision support system using the Multi-Attribute Utility Theory (MAUT) method effectively and assist in the process of selecting prospective chairman candidates objectively by being able to complete calculations based on the conditions or supporting aspects they have. The MAUT method is used to resolve the complexity of decision making in selecting a prospective chairman. The application of the MAUT method can provide recommendation results as a candidate for OSIS chairman in ranks 1 - 3 with the largest total results of 0.706 for A8, 0.689 for A2 results and 0.63 for A10 results, while ranks 4 - 6 as deputy chairman of OSIS with a value of 0.624 for A5, a value of 0.523 for A1 and 0.51 for the alternative A3 to then become a pair of candidates who will be selected directly using the E-Voting system. this system can make a significant contribution in increasing transparency, efficiency and validity in the democratic process in the school environment.